1994
DOI: 10.1002/app.1994.070520805
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structure and dynamic mechanical behavior of silk fibers modified with different kinds of epoxides

Abstract: SYNOPSISThe chemical reactivity of epoxide molecules toward silk fibroin was investigated by determining the rate of conversion of reactive amino acid residues. Significant differences were found between two different bifunctional epoxides, diglycidyl ethers of ethylene glycol ( E ) and resorcinol (R) , the former reacting at a higher extent with arginine and tyrosine.The moisture regain decreased by reaction with epoxides, at a variable rate and extent, according to the hydrophobic/hydrophilic properties of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Among the basic amino acid residues, lysine and histidine significantly decreased. These results are similar to other studies [8][9][10][11].…”
Section: Resultssupporting
confidence: 93%
“…Among the basic amino acid residues, lysine and histidine significantly decreased. These results are similar to other studies [8][9][10][11].…”
Section: Resultssupporting
confidence: 93%
“…Silk fibroin is composed of 16 amino acids. The basic Table 2 The amino acid content of fibroin amino acid content of fibroin (0.849%) is much smaller than in wool keratin (22%) ( Table 2) [5,6].…”
Section: Reactive Centres In Silk Fibre Involved In the Dyeing Processmentioning
confidence: 99%
“…Various approaches have been used to modify silk broin with functional groups, and the resulting materials have been used for bio-applications, including tissue engineering and drug delivery. 19,20 Another such study demonstrated that tyrosine residues could be modied by electrophilic aromatic substitution. Numerous studies have exploited reactive amino acid residues, such as serine and/or lysine, to introduce functional groups on silk backbones by utilizing coupling methods with reagents such as cyanuric chloride derivatives, [11][12][13][14] carbodiimides, [15][16][17] alkoxysilanes, 18 and epoxides.…”
Section: Introductionmentioning
confidence: 99%